Jak długo Jezus był w łonie Maryi? Opinie Ojców Kościoła - Naumowicz, Józef (Vox Patrum, 2008)
The time from the conception to the birth of Jesus is most often given as nine or ten months. Sometimes one and the same author gives both numbers without any explanation, for example Tertullian, Zeno of Verona, Ambrose of Milan or Jerome. However there is no contradiction between the two. „Ten months” refers to lunar months (28 days), and corresponds to nine months in the solar calendar. The ecclesiastical authors used the formula „ten (lunar) months” not only be-cause they wanted to follow Virgil, as Adkin suggests. It appears also in the writings of pagan authors of late antiquity, and survived as a set phrase in everyday language into times when the lunar calendar was no longer used (with the exception of the Christian reckoning of Easter, which continued to be based on lunar cycles). Another matter are the opinions reported by Epiphanius in the Panarion, that Jesus was born seven (according to the Alogi) or nine and a half months after conception. These opinions arose no doubt from numerological speculation, but the length of pregnancy is also reckoned in lunar months. This shows that in late antiąuity the expression „ten months” was not merely a formula. Lunar months were still used and understood, particularly if it was to give the length of time spent by a child in its mother’s womb.